Prauserella cavernicola sp. nov., isolated from cave rock. Issue 11 (22nd November 2021) - Suriyachadkun, Chanwit; Ngaemthao, Wipaporn; Pujchakarn, Tawanmol; Mhuantong, Wuttichai; Chunhametha, Suwanee
Abstract : A novel actinomycete, designated strain ASG 168 T, was isolated from cave rock collected from Stegodon Sea Cave in Thailand. Long chains of non-motile spores that were oval or spherical in shape with a smooth surface developed on aerial mycelia. Substrate mycelia fragmented into irregular rod-shaped elements. A polyphasic taxonomic study showed that strain ASG 168 T had typical characteristics of members of the genus Prauserella . 16S rRNA gene sequence analysis indicated that strain ASG 168 T shared 97.5 % similarity with Prauserella marina MS498 T and 96.7 % with Prauserella coralliicola SCSIO 11529 T . Average nucleotide identity values with P. coralliicola SCSIO 11529 T and P. marina MS498 T were 82.98 and 76.08 %, respectively. The cell-wall peptidoglycan contained meso -diaminopimelic acid. The whole-cell sugars contained ribose, arabinose and galactose. The predominant menaquinone was MK-9(H4 ). The predominant fatty acids were iso-C16 : 0, C16 : 0 and summed feature 3 (C16 : 1 ω 7 c /C16 : 1 ω 6 c ). The phospholipid profile consisted of phosphatidylethanolamine, phosphatidylmethylethanolamine, diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol, phosphatidylinositol mannosides and two unknown phospholipids. The G+C content of the genomic DNA was 70.6 mol%. Differentiation of strain ASG 168 T from closely related species was evident from digital DNA–DNA hybridization values of 29.2 and 21.3 % with P. coralliicola and P. marina, respectively. Based on comparative analysis of phenotypic, chemotaxonomic and genotypic data, the novel actinomycete strain ASG 168 T (=TBRC 13679 T =NBRC 114887 T ) is proposed to be the type strain of a novel species, Prauserella cavernicola sp. nov.